PreImplantation Factor (PIF) correlates with early mammalian embryo development-bovine and murine models - Coulam Carolyn B; Goodman Chelsi; Ramu Sivakumar; Absalon-Medina Victor; Stout Mike; Roussev Roumen G; Stamatkin Christopher W; Gilbert Robert O; Godke Robert A; Barnea Eytan R (BMC, 2011)
Abstract Background PreImplantation Factor (PIF), a novel peptide secreted by viable embryos is essential for pregnancy: PIF modulates local immunity, promotes decidual pro-adhesion molecules and enhances trophoblast invasion. To determine the role of PIF in post-fertilization embryo development, we measured the peptide's concentration in the culture medium and tested endogenous PIF's potential trophic effects and direct interaction with the embryo. Methods Determine PIF levels in culture medium of multiple mouse and single bovine embryos cultured up to the blastocyst stage using PIF-ELISA. Examine the inhibitory effects of anti-PIF-monoclonal antibody (mAb) added to medium on cultured mouse embryos development. Test FITC-PIF uptake by cultured bovine blastocysts using fluorescent microscopy. Results PIF levels in mouse embryo culture medium significantly increased from the morula to the blastocyst stage (ANOVA, P = 0.01). In contrast, atretic embryos medium was similar to the medium only control. Detectable - though low - PIF levels were secreted already by 2-cell stage mouse embryos. In single bovine IVF-derived embryos, PIF levels in medium at day 3 of culture were higher than non-cleaving embryos (control) (P = 0.01) and at day 7 were higher than day 3 (P = 0.03). In non-cleaving embryos culture medium was similar to medium alone (control). Anti-PIF-mAb added to mouse embryo cultures lowered blastocyst formation rate 3-fold in a dose-dependent manner (2-way contingency table, multiple groups, X2; P = 0.01) as compared with non-specific mouse mAb, and medium alone, control. FITC-PIF was taken-up by cultured bovine blastocysts, but not by scrambled FITC-PIF (control). Conclusions PIF is an early embryo viability marker that has a direct supportive role on embryo development in culture. PIF-ELISA use to assess IVF embryo quality prior to transfer is warranted. Overall, our data supports PIF's endogenous self sustaining role in embryo development and the utility of PIF- ELISA to detect viable embryos in a non-invasive manner.